Introducing qualified majority voting in the common foreign and security policy - Udovič, Boštjan (Journal of comparative politics, 2025)
The article examines the positions of Slovenia and Slovakia on introducing qualified majority voting in the area of the Common Foreign and Security Policy (QMV CFSP). This topic has gained significance in recent years due to various attempts to obstruct decision-making within the European Union. The analysis is conducted on two levels: Official government statements from both countries and the perceptions of students on the issue. The findings reveal a stark contrast between the two levels. While Slovenia and Slovakia hold opposing official positions on QMV CFSP, students from both countries largely support its introduction. However, there is a notable difference regarding QMV CFSP as a preliminary step towards deeper integration: Slovak students are somewhat more reserved than their Slovenian counterparts. This suggests that the political discourse in Central and Eastern Europe, particularly concerns over the ‘dangers of EU deepening’, is influencing younger generations and the student population.
Keywords: Evropska unija; glasovalni sistem; Glasovanje; kvalificirana večina; Skupna zunanja in varnostna politika